Capturing complexity in how configurations of firm Internal Orientations impact corporate social performance outcomes: Breaking from the dominant logic of symmetric-variable to asymmetric-case-based theory and testing - Isaksson, L.; Woodside, Arch (Elsevier, 2016)
This study exemplifies how an asymmetric and case based (configurational) research approach (using fuzzy state logic and complexity theory) is useful for conceptualization and explanation of complex topics and heterogeneous outcomes. The study here analyses the recipes (condition combinations) for Internal Orientation constructs (IO: strategic intent, CSP management, strategic orientation and industrial standards) among multi-national companies (MNCs) indicating “high” levels of corporate social performance (CSP) and the “United Nations Principles for Responsible Investment” (UNPRI) ESG factor framework (Environment, Social-human rights, and Governance) – separately and as a whole. The study applies a mixed methods research design and includes comparing ESG with financial performance across a “Top-100 Sustainable Companies Index” (n?=?82 of MNCs trading on the Swedish stock exchange). The study's findings support the core tenets of complexity theory; all four IO constructs affect a high E or S or G outcome but not all three outcomes in combination.